The throne of fire - Riordan, Rick. (New York : Disney/Hyperion Books, 2011)
Carter Kane and his sister must prevent the chaos snake Apophis from breaking free in a few days' time or the world will come to an end. To have any chance of battling these Forces of Chaos, the Kanes must revive the sun god Ra.
Keywords: Mythology, Egyptian -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Voyages and travels -- Juvenile fiction; Magic -- Juvenile fiction; Mythology, Egyptian -- Fiction; Brothers and sisters -- Fiction; Voyages and travels -- Fiction; Adventure and adventurers -- Fiction; Magic -- Fiction; Fantasy; Voyages and travels -- Fiction; Egyptian mythology -- Fiction; Magic -- Fiction; Siblings -- Fiction; Young adult fiction; Adventure stories; Adventure fiction